EFEKTIVITAS PENERAPAN AKUNTANSI SYARIAH DALAM SISTEM PERBANKAN DIGITAL (STUDI KASUS BSI PALEMBANG) - Nia Permata Sari; Siti Nurhayati Nafsiah (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Dharmawangsa, 2026)
The development of digital technology has led to significant changes in the banking sector, including Islamic banking in Indonesia. The digitalization process requires the use of sharia accounting that is not only accurate and efficient, but also adheres to sharia principles. This study aims to assess the effectiveness of Sharia accounting in the digital banking system at Bank Syariah Indonesia (BSI) Palembang and to identify the factors that support and hinder its implementation. This study employs a descriptive qualitative approach and gathers data thru interviews, observations, and documentation. The participants in this study are the management and employes of BSI Palembang who are directly involved in the bank's digital operations. Data analysis was conducted using the steps of data reduction, data presentation, and drawing conclusions, while data validity was tested using the triangulation method. The study results indicate that the implementation of Islamic accounting in digital banking at BSI Palembang has been carried out well. This is evident in compliance with Sharia Financial Accounting Standards (SFAS), the application of the principles of trust and transparency, and the avoidance of usury, uncertainty, and gambling. The digitalization process can improve timeliness, accuracy, operational efficiency, and information transparency for customers. Nevertheless, the quality of human resources and the security of digital systems still remain issues that need to be improved.